Critical Reflection on Sexuality Research in Nigeria: Epistemology, Fieldwork and Researcher's Positionality - Alabi, Oluwatobi (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2023)
Within various African cultures, discussion of sexuality is typically secretive and reticent. Because of the multiple and sometimes contradictory narratives about sexuality, researching it in this context remains a very sensitive and knitted terrain, requiring careful navigation of historical, sociocultural and religious factors. The state of such scholarship in Nigeria is here explored critically, drawing on my experience of studying traditional aphrodisiacs in Ilorin. In this article, I present a reflection on the epistemological grounding of that work, my positionality and fieldwork experience, as well as the dilemmas, challenges and the politics of researching sexuality in Nigeria. I argue that the complexity of a researcher's identity and embodiments is not to be treated as redundant; instead, it needs to be taken into account in legitimate and productive ways. Focusing on these elements and experiences during fieldwork revealed how researchers can have the opportunity to contour, compound and contribute to a qualitative study. Investigators must be self-aware and constantly reflexive through this process.